Evaluasi Kerentanan Akuifer Menggunakan Metode Simple Vertical Vulnerability Berdasarkan Hasil Penyelidikan Geolistrik (Studi Kasus di Desa Sumberpasir, Kecamatan Pakis, Kabupaten Malang) - Julia Putri Rosalinda; Hari Siswoyo; Sri Wahyuni (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
There are indications of water pollution due to industrial waste, which can be seen from the rivers and springs condition in Sumberpasir Village. So it is necessary to investigate the vulnerability of the aquifer using SVV method. There are three parameters that must be calculated as the index value of the SVV method, thickness of the unsaturated zone, percolation value, and material type of the unsaturated zone. From the three parameter values, the SVV index will be obtained as an aquifer vulnerability assessment. The SVV index was mapped into the distribution of aquifer vulnerability using the Surfer program. The results of the study resulted in five types of rock lithology materials as a result of interpretation from geoelectrical investigations based on adjustments to actual conditions in the field. The layer with the lowest resistivity is clay, the second layer is tuff, the third layer is sandy tuff, the fourth layer is pumice, and the fifth layer is breccia. From the three parameters of the SVV calculation, the SVV index value is between 54 which is interpreted as having a moderate vulnerability until 76 with a very low vulnerability. So that Sumberpasir Village is considered likely to be safe against aquifer vulnerability. The distribution of vulnerability levels in the research location is divided into three, very low vulnerability (18.65% of the total area Sumberpasir Village), low vulnerability (60.03%), and medium vulnerability (21.32%).